1999
DOI: 10.1002/(sici)1097-4636(199907)46:1<44::aid-jbm5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bioprosthetic heart valve failure: Fatigue causes collagen denaturation and glycosaminoglycan loss

Abstract: Bioprosthetic heart valve (BPHV) degeneration, characterized by extracellular matrix deterioration, remodeling, and calcification, is an important clinical problem accounting for thousands of surgeries annually. Here we report for the first time, in a series of in vitro accelerated fatigue studies (5-500 million cycles) with glutaraldehyde fixed porcine aortic valve bioprostheses, that the mechanical function of cardiac valve cusps caused progressive damage to the molecular structure of type I collagen as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 25 publications
2
80
0
Order By: Relevance
“…1,2 Thus, the spongiosa layer plays a significant role in reducing valve mechanical fatigue. 1,2 Moreover, this layer is constantly remodeled in native valves to maintain the valve's mechanical properties. 1 Conventional glutaraldehyde crosslinking of porcine aortic valves significantly reduces flexural properties of native valves.…”
Section: Significance Of Heart Valve Tri-layered Structurementioning
confidence: 99%
See 3 more Smart Citations
“…1,2 Thus, the spongiosa layer plays a significant role in reducing valve mechanical fatigue. 1,2 Moreover, this layer is constantly remodeled in native valves to maintain the valve's mechanical properties. 1 Conventional glutaraldehyde crosslinking of porcine aortic valves significantly reduces flexural properties of native valves.…”
Section: Significance Of Heart Valve Tri-layered Structurementioning
confidence: 99%
“…[1][2][3] We have recently reported that glycosaminoglycans (GAGs) present in the middle spongiosa layer of BPHV leach out under in vitro cyclic fatigue, resulting in a significant reduction in cuspal stiffness, thus making BPHV cusps vulnerable to material failure. 2 In the native valve, highly hydrated GAGs present in the middle spongiosa layer allow shearing between the two outer layers, the fibrosa and ventricularis, during valve function. 1,2 Conventional glutaraldehyde crosslinking does not stabilize GAGs present in BPHVs because the structures of hyaluronic acid (HA) and dermatan sulphate (the major GAGs present in the BPHV cusps) do not have the amine functionalities necessary to react with glutaraldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered proportions of selected PGs and GAGs are found in myxomatous MV disease [5], are probably responsible for the altered material properties of these swollen tissues [6], and are possibly involved in the disease pathogenesis. The loss of the GAG-and PG-rich spongiosa layer, which normally provides shear between the outer valve layers and thus enables complex valve leaflet movement [7], from porcine bioprosthetic aortic valves (AVs) is thought to be instrumental in the failure of these devices [8]. Overall, knowledge of the composition and distribution of the various GAGs and PGs within heart valves appears to be essential for understanding and recapitulating the complex mechanics of the heart valve leaflets.…”
Section: Introductionmentioning
confidence: 99%